Analisis Peran Account Officer dalam Menekan Pinjaman Bermasalah di PT BPR NBP 9 Pangururan - Kenedy, Olivia Agatha; Sitorus , Jessy Safitri (Jurnal Ekonomi Bisnis Digital, 2022)
Non-performing loans are one of the risks that will be faced by financial institutions, including at PT BPR nbp 9 Pangururan. This risk arises because of the inability of borrowing customers to pay part or all of the loan agreements that have been mutuallyagreed upon, there are many ways that can be done in overcoming non-performing loans, in this case the role of the Account Officer is very much needed, because from the beginning of the loan application process to the strategy to resolve if something happens. non-performing loans are resolved by the Account officer. In addition, good loan management and Account officers who are involved in monitoring the business run by customers can also reduce at least the risk of non-performing loans. The role of the Account Officer is needed in resolving non-performing loans in financial institutions. The purpose of this study was to analyze the role of the accountant officer in suppressing non-performing loans at PT BPR nbp 9 Pangururan. This type of research is qualitative, namely a study that describes the analysis of the role of account officers in suppressing non-performing loans at PT BPR nbp 9 Pangururan